2011
DOI: 10.1155/2011/438056
|View full text |Cite
|
Sign up to set email alerts
|

Practices in Wound Healing Studies of Plants

Abstract: Wounds are the result of injuries to the skin that disrupt the other soft tissue. Healing of a wound is a complex and protracted process of tissue repair and remodeling in response to injury. Various plant products have been used in treatment of wounds over the years. Wound healing herbal extracts promote blood clotting, fight infection, and accelerate the healing of wounds. Phytoconstituents derived from plants need to be identified and screened for antimicrobial activity for management of wounds. The in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
196
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(231 citation statements)
references
References 73 publications
6
196
0
11
Order By: Relevance
“…Tannins act as free radical scavengers (Thakur et al, 2011) and 55% of overviewed plants in our study contain tannins. Triterpenoids and flavonoids promote wound healing due to their astringent and antimicrobial properties (Thakur et al, 2011) and we found that 45% of our plants overviewed contain terpenoids.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Tannins act as free radical scavengers (Thakur et al, 2011) and 55% of overviewed plants in our study contain tannins. Triterpenoids and flavonoids promote wound healing due to their astringent and antimicrobial properties (Thakur et al, 2011) and we found that 45% of our plants overviewed contain terpenoids.…”
Section: Discussionmentioning
confidence: 67%
“…Tannins act as free radical scavengers (Thakur et al, 2011) and 55% of overviewed plants in our study contain tannins. Triterpenoids and flavonoids promote wound healing due to their astringent and antimicrobial properties (Thakur et al, 2011) and we found that 45% of our plants overviewed contain terpenoids. Saponins, due to their antioxidant and antimicrobial activity (Thakur et al, 2011), appear to be responsible for wound contraction and elevated rate of epithelialization; they are present at a level of 36% in these overviewed plants.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In many parts of "frica, divination is widely practiced [51]. It is used as a means to understand the complexities of life and avoid catastrophe.…”
Section: Divinationmentioning
confidence: 99%